Drawn Legality. Notes on Non-Textual Rules and Criminal Law - Bottalico, Filippo (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
The work aims to investigate – from a peculiar criminal law perspective – the constitutive-pragmatic and not only epistemic relevance of non-textual rules, which accompany the usual textual rules in different areas of the legal system. If traditionally social objects are inscribed in linguistic-verbal propositions, nevertheless the construction of social reality abounds with examples of non-textual rules. Once the possibility of theoretically conceiving social objects descended from non-textual provisions has been probed, the investigation identifies a working hypothesis to reconcile – in the criminal law context – this conclusion with the principle of legality. The analysis continues with an example of three different hypotheses of non-textual rules: non-textual rules integrating textual rules (the example is the road signals); non-textual rules complementary to textual ones (the example is the workplace health and safety signals); finally, autonomous non-textual rules (the example is the project). Parole chiave: Rules; Text; Drawing; Legality; Law Indice: 1. Suggestioni – 2. Documentalità, testualità e idiomaticità – 3. Le disposizioni non testuali nella prospettiva penalistica. Ipotesi di lavoro – 4. Disposizioni non testuali integratrici di disposizioni testuali: l’esempio della segnaletica stradale – 5. Disposizioni non testuali complementari di disposizioni testuali: l’esempio della segnaletica di salute e sicurezza sul lavoro – 6. Disposizioni non testuali autonome: l’esempio del progetto